Formation of Human Subjectivity in Psychological Interactions with Nature - S A Mudrak; A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2014)
The article outlines the current trends in the environmental psychological research of the peculiarities of developing the subject-subjective human relationship with nature: considering human habitat environment as a set of natural objects; studying certain natural sites as psychologically attributive elements of the environment; determining the psychological meaning of the «Human Habitat Environment»; giving the analysis of the problem of the subjectivity development in human interaction with the natural objects.